2023
DOI: 10.1007/s11357-023-00927-x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models

Ka Ka Ting,
Paul Coleman,
Hani Jieun Kim
et al.

Abstract: Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of Alzheimer's disease [69,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer's disease have been investigated . Numerous studies are also available regarding treatments with probiotics [139][140][141][142].…”
Section: Discussionmentioning
confidence: 99%
“…These circulating substances trigger an immune response, leading to sterile inflammation in tissues, enhancing the production of inflammatory factors (resulting in subclinical inflammation at the systemic level), and potentially serving as the basis for autoimmune processes [ 67 ]. It is likely that chronic low-grade sterile inflammation also plays a role in age-related alterations in the cerebral microcirculation, contributing to the pathogenesis of vascular cognitive impairment [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Probiotics play a crucial role in directly inhibiting inflammation threatening the nervous system and may prevent the circulation of substances that activate the immune system [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs degrade several key ECM components that are important in maintaining integrity of the vessel wall, such as elastin, fibronectin, and laminin. Previous research showed that the degradation of elastin preceded VSMC loss and vascular calcification in a model of CKD [86] . Therefore, enhanced matrix degradation, induced by SASP, could contribute to vascular calcification.…”
Section: Aging and Senescencementioning
confidence: 91%
“…Stroke is a vascular disease and vascular senescence causes a myriad of downstream effects on the integrity of the BBB. BBB permeability is an early feature of age-related diseases, including Alzheimer’s disease, due to vascular senescence [ 74 , 84 ]. Chronic inflammation induced by SASP activation increases BBB permeability [ 85 ], reduces neurogenesis, and adversely affects cognitive performance [ 86 ].…”
Section: Role Of Senescence/sasp In Ischemic Strokementioning
confidence: 99%